iAWARE: Um modelo para Cuidado ubíquo de Pacientes com Transtornos de Ansiedade, Depressão e Estresse utilizando Gamificação e Biodata - Dias, Lucas Pfeiff er Salomão; Barbosa, Jorge Luis Victória (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Depression and anxiety are the most prevalent mental disorders, reaching million people worldwide. As they share many characteristics these two disorders can manifest themselves together. In addition, stress is one of the related factors with both depression and anxiety, being relevant in the analysis of these disorders. This paper proposes a model for ubiquitous care of patients with depression, anxiety and stress disorders (DASD) using gamification and biodata, called iAware. A/B tests evaluated with a clinical population the interaction engagement of the patient to the treatment provided by gamification. Based on the patient’s history, the iAware monitors and applies interventions for the patient at the most appropriate time. Six patients used a prototype with a smartband for two weeks to evaluate iAware. Interactions with intervention stages were greater in patients who used iAware gamified. A more detailed analysis is still required. The evaluated patients got more occurrences of anxiety at home. The patients also filled out a survey based on the Technology Acceptance Model (TAM). TAM results show that patients have found the iAware useful in their anxiety treatment routines.